Características físico-químicas de las aguas de los afluentes del Embalse Arenal, Costa Rica y su relación con el plancton - Paaby, Pia (Universidad de Costa Rica, 1995)
The Arenal watershed (NW Costa Rica) is comprised of (1) the Caño Negro and Chiquito rivers and (2) the Sábalo, Piedras, Jilguero, Aguacate, Rugama and Dos Bocas stream systems. The first system is cbaracterized by higher values of total suspended solids, conduCtivity, pH, dissolved oxygen, nitrate and phosphonis, as well as lower temperatures than the second system of streams. Because of morphometrical and depth differences throughout the length of too receiving reservoir, the effect of the varioUs affluents on plancton population population dynamics are hypothesized lo vary accordingly.